(untitled) (Journal of Computational Intelligence and Robotics, 2024)
Multi-robot systems (MRS) have gained significant attention for their potential to accomplish complex tasks efficiently and robustly. Coordination and communication are key aspects in ensuring the successful operation of such systems. This paper provides a comprehensive review of the existing literature on coordination and communication mechanisms in MRS. We discuss various approaches, including centralized, decentralized, and distributed methods, highlighting their strengths and limitations. Additionally, we explore the role of communication in enabling effective coordination among robots, considering factors such as bandwidth, latency, and reliability. Furthermore, we examine emerging trends and future directions in MRS coordination and communication, including the integration of artificial intelligence and machine learning techniques. Overall, this paper aims to provide insights into the state-of-the-art in MRS coordination and communication, offering guidance for researchers and practitioners in the field.